Associations of Self-efficacy, Family Support, Peer Support, and Posyandu Facility, with Mother - Ernawati, Ernawati; Sulaeman, Endang Sutisna; Indarto, Dono (Journal of Maternal and Child Health, 2018)
Background: Integrated service delivery has been defined as